2010
DOI: 10.1108/09526861011010695
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and wellbeing of the elderly in Lebanese nursing homes

Abstract: The study is original in the sense that it assesses elderly residents' psychological and physical health status in relation to institutional structures, processes, and skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 34 publications
(45 reference statements)
5
49
2
Order By: Relevance
“…In the current study nutritional status was associated with all EQ-5D-3L dimensions, even though no previous work has been found that assessed this relationship among T2DM patients, our results are consistent with other reports which have examined nutrition and HRQoL in a smaller community-based study (37), in other selected older adults populations (38) and a population sample studies in older adults (39). The findings from our study and the cited work strengthened our understanding of the relationship between the risk for malnutrition and reduced HRQoL.…”
Section: Discussionsupporting
confidence: 93%
“…In the current study nutritional status was associated with all EQ-5D-3L dimensions, even though no previous work has been found that assessed this relationship among T2DM patients, our results are consistent with other reports which have examined nutrition and HRQoL in a smaller community-based study (37), in other selected older adults populations (38) and a population sample studies in older adults (39). The findings from our study and the cited work strengthened our understanding of the relationship between the risk for malnutrition and reduced HRQoL.…”
Section: Discussionsupporting
confidence: 93%
“…This is contrary to previous researches which show that women have longer life expectancy and spend a greater total number of years in good health than men; however, wo men spend a greater proportion of the older years in poor health than men [27,28]. Another study found that elderly married males enjoy better health than the elderly females [29]. The study concluded that the traditional role that wo men play as the primary care givers, coupled with the lower status leave them with access to limited financial resources and health care for themselves.…”
Section: Discussioncontrasting
confidence: 55%
“…Distribution of the sample according to the socio-demographic characteristics of the elderly indicates that 73.1% of male have moderate and more severe levels of depressive symptoms than female have; 60 years old and more, 53.9% of primary and secondary levels of school, 67.3% of married, and 42.3% of retired are likely to have moderate level (Tables 3,4 Table 8). Many previous studies revealed high prevalence of depressive symptoms in elderly living in nursing homes; more than three to four times greater than the non-nursing-homes elderly (15)(16)(17)(18)(19)(20)(21)(22) . By applying the short form of Geriatric Depression Scale (GDS-15) (1) , an additional comprehensive and valuable scoring scheme in rating depressive symptoms, the present study categorized the status of depressive symptoms among elderly sample into three levels: normal, moderate, more severe depressive symptoms according to a 3-cut-off points.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire consisted of two parts: firstly, five sociodemographic characteristics of elderly: gender, age, level of education, occupation and marital status; and second part is fifteen items which are supposed to assess levels of depressive symptoms and represent Geriatric Depression Scale (GDS-15) for Almeida (1999) (1) which is to define the levels of depressive symptoms among those elderly. The 15-item GDS (GDS-15) is a short version of the original Geriatric Depression Scale (GDS), developed by Sheikh & Yesavage (1986) (15) from items more strongly linked to the recognition of depressive symptoms. Overall, GDS items have revealed good diagnostic accurateness in addition to acceptable understanding, precise and reliability.…”
Section: Methodsmentioning
confidence: 99%